Uncovering the backings to passion: Why do small firm owners/managers engage in entrepreneurship? - Abdella Kosa; Idris Mohammed (Journal of Innovation and Entrepreneurship, 2017)
This study aimed to uncover the backings to passion that plays a great role on firm's entrepreneurial engagement. It explores a framework on what other factors determine the individual's engagement on entrepreneurship. To meet this, data's were collected from a sample of 112 firms and analyzed using descriptive and hierarchical linear regression analysis. The finding reveals that, Even if passion has a great impact on entrepreneurial engagement; it may not be successful without consideration of both their internal resource and external environments. The presence of human and financial capital as well as government supports intensifies the engagement of firms in entrepreneurship, while the unpredictability of environment hinders the successful practice of entrepreneurship. These are not the only factors that intensify the relationship; therefore, the future research should add other determinants such as technology diffusion and marketing environment and test on longitudinal study to capture the trends of individual firm's engagement.
Keywords: 650; Entrepreneurial; Engagement; Environment; Passion; Resource